Tradução e adaptação cultural da “Family Meaning of Nursing-Home Visits Scale/Escala de Significado Familiar de Visitas a Instituições de Longa Permanência para Idosos” para o contexto brasileiro - Andrade, Larissa de (Universidade Federal de São Carlos, 2021)
Introduction: The demand for services provided by Long-Term Institutions for the Elderly (LTCIs) grows with the aging of the population. These spaces can represent a positive alternative of protection, protection and security, or a negative one that symbolizes the abandonment of a loved one. In the context of LSIEs, one of the ways to maintain the family bond is through family visits. Recently, a scale was built and validated in Taiwan in order to understand the meaning attributed by families to visiting institutionalized elderly people, called the Family Meaning of Nursing - Home Visits Scale (FMNHVS). The availability of this instrument in Brazil is justified by the increasing number of elderly people living in LSIE and the importance of family ties that directly affect the biopsychosocial conditions of the elderly. Objective: To translate and culturally adapt the FMNHV scale to the Brazilian context. Materials and methods: This is a methodological study, in which the steps recommended in the international literature were followed, which are: initial translation, synthesis of translations, back translation, review by a committee of judges and pre-test. Results: The initial translation was performed by two professional translators with experience in scientific texts in the health field. The synthesis of the translations was carried out through a meeting between members of the research group and the translators for a consensus on the differences found. The back-translation consisted of translating the FMNHVS back to the original language and submitting it to the original author for consideration. After approval and consensus with the author, a committee of six judges reviewed and compared all translations performed. There was an agreement of 83% for all items and a version for the pre-test was reached in Brazil. The pre-test stage consisted of applying the instrument to a sample of family members of institutionalized elderly in order to assess all the items on the scale, in terms of clarity and understanding of the questions, in order to identify errors and adapt to the context. Brazilian. Conclusion: The instrument was considered clear and understandable and no changes were necessary. The Brazilian version of the FMNHVS was translated and culturally adapted to the Brazilian context.
Translation and cultural adaptation of the “Family Meaning of Nursing - Home Visits Scale” for the brazilian context
Keywords: Idosos; Instituição de Longa Permanência para Idosos; Relações familiares; Tradução; Inquéritos e questionários; Elderly; Long-Term Institution for the Elderly; Family relationships; Translation; Surveys and questionnaires; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE